Validation worksheet students of science assisted by education card based on science edutainment - Renti Surya; Djusmaini Djamas; Yulkifli (Fakultas Ilmu Pendidikan UNP)
Learning process is a fun activity where learners have the freedom to actualize themselves, develop the potential in accordance with the talent and develop it. It demands educators to be creative in creating teaching materials and media. Teaching materials that can be collaborated with the media is a worksheet student of science asissted by education card based on science edutainment. The purpose of this paper is to produce a worksheet student of science asissted by education card based on science edutainment that is valid, practical and effective. The development model used is a Plomp development model consisting of three stages of initial investigation, development and assessment phase. The validity test is at the development stage. Validity test is done through validation sheet. The result of validity test shows the a worksheet student of science asissted by education card based on science edutainment developed in valid category. Then product can be applied in learning and able to overcome all problems.